Progressive failure analysis of U-notched thin composite plates repaired with a double-sided composite patch - Uslu, Merve; Kaman, Mete Onur (Sage Publications Ltd, 2023)
In this study, carbon fiber-reinforced U-notched composite plates were repaired with composite patches made of the same material using adhesive bonding and their mechanical performance was investigated experimentally and numerically. Repairs were made by applying a double-sided composite patch to the notched thin composite plates. The repaired composite plates were tested under tensile load. The effect of the variation in notch width and depth on the repaired plate failure load and type was investigated. At the end of the experiments, load-displacement graphs of each specimen were obtained. The effect of variation in notch depth and width in the repaired specimens was not as dominant as in the non-repaired specimens. While the variation in notch dimensions changed the failure load between 34% and 37% in the non-repaired specimens, this rate was between 18% and 21% in the repaired specimens. In the numerical analysis, progressive failure analysis was performed using the Hashin Failure Criteria. Subroutine codes were written in the program Ansys, which uses the finite element method for numerical analysis. In the results, numerical and experimental load-displacement graphs and failure types of the specimens are presented comparatively. The convergence rate of the experimental and numerical data was between 92% and 99.8%.
Keywords: Hashin; patch; laminated composite; notch; progressive failure analysis